Assessment of Rubber Industry Smallholders Development Authority (RISDA) service quality in Negeri Sembilan - Agustina, Dwi Shinta; Abdullah, Amin Mahir; Mohamed, Zainal Abidin; Kamarulzaman, Nitty Hirawaty (Malaysian Agricultural Research and Development Institute (MARDI), 2009)
Smallholders play an important role in the rubber sub-sector in Malaysia. Realizing the importance of this group in the industry, the government established RISDA to organize them and provide replanting assistance. Hence, providing adequate service quality is a vital responsibility for RISDA in order to increase the capability of smallholders, especially in increasing their productivity which subsequently increase their income. The aim of this study was to determine the level of smallholders’ satisfaction towards the services delivered by RISDA. The measurements used were based on widely accepted service quality model (SERVQUAL). Questionnaires used in this study were limited to a sample of 98 respondents in the western region of RISDA’s administration in Negeri Sembilan. A descriptive statistics analysis was used to describe the level of services rendered by RISDA. Service quality gaps were determined by computing the differences between customers’ expectations and their actual perceptions. The results of the study indicated that the overall service quality provided by RISDA was below smallholders’ expectations. Tangible dimension was the most critical dimension of service quality delivered by RISDA while assurance dimension was the least critical dimension.